Utilizing disposable masks as effort to manage household waste to create cherry blossom bonsais - Inggit Marodiyah; Atikha Sidhi Cahyana; Intan Rohma Nurmalasari; Wiwik Widhianingsih; Dewi Fortuna Kusuma (Community Empowerment, 2023)
Garbage is one of the main issues that harm the environment, especially inorganic waste such as disposable masks. Innovative ways to manage or recycle single-use masks need to be implemented. This community service aims to increase public knowledge about the dangers of waste and how to recycle household waste into products with a sale value. The waste is processed into handicrafts in the form of cherry blossom bonsai. The method of implementing community service was training in making cherry blossom bonsai from disposable masks which was attended by PKK women from Kajartengguli Village, Prambon District, Sidoarjo Regency. The result of this program is that partners can recycle disposable mask waste into cherry blossom bonsai. This product can be used to decorate a living room table or work table and can reduce the amount of solid waste generated by households. In addition, this program can increase awareness of the cleanliness of the surrounding environment.